A legal study on cyber piracy : protection of software copyright in Malaysia / Norazizah Sineng, Mazaitul Norli Maisarah Mohd Ramly and Fara Hidayatul Aqma Abdul Ghani - Sineng, Norazizah; Mohd Ramly, Mazaitul Norli Maisarah; Abdul Ghani, Fara Hidayatul Aqma (Faculty of Law, 2011)
In Malaysia, the infringement of software copyright is a problem that still cannot be curbed from the nature of the citizens. Even though we have regulations that are related to software copyright, the enforcement of the regulation in our country is still inadequate which had caused many infringements of copyright issues. Compared to the United Kingdom, we found that country is really strict with regard to this matter. Thus, our country is facing a problem on protection of software copyright due to the changes of the industry in relation to the demand for new and better software. As a result, our industry is threatened by the scale of cyber piracy. This happens when there is no proper enforcement and effectives law that governs this industry. This high price of computer software in the market will also lead people to pirate the software easily by using the Internet. The Copyright Act 1987 of Malaysia provides comprehensive protection for copyrightable works. The Act outlines the nature of works eligible for copyright which include computer software, the scope of protection, and the manner in which the protection is accorded. The Copyright Act 1987 also provides the enforcement of the law by the Ministry of Domestic Trade, Co-operatives and Consumerism (MDTCC). In addition, the Act also provides the necessary clout to the enforcement agencies to effectively carry out anti-piracy measures. The Act is currently being amended to expand the power of the tribunal to include arbitration of disputes relating to use of copyright works. In relation to this study, our main scope is on the protection of software copyright in Malaysia. The aims of our studies are to critically analyze the law relating to software copyright in Malaysia, how the Copyright Act 1987 protects the software copyright in Malaysia and to examine the weaknesses by comparing the law in other countries such as the United States of America and the United Kingdom. As for the result outcome, we wish to find possible suggestions in order to improve the enforcement of software copyright in Malaysia. Therefore, a comparison should be made with the United States and the United Kingdom in order to adopt their effectiveness in the enforcement of the law in our country, Malaysia.